Hydrocarbon Degrading Potential of Microbes Isolated from Industrial and Domestic Sources - Saadon, Shazleen (Universiti Teknologi Petronas, 2011)
A research is conducted to scrutinize the capability of microbial species to degrade crude oil. This study is carried out in relation to the major destructive environmental problem occurred today, the oil spill contamination. For decades scientists and researchers have been trying to find the solution to the oil spill problem in order to preserve the marine environment. Bioremediation technique is one of the most cost effective and efficient methods; in which microbes are utilized to degrade the oil spill by digesting the hydrocarbon as their sole carbon source and energy. There are substantial amount of studies verifying the competency of microbe strains isolated from crude oil contaminated sites to degrade the hydrocarbons chain, but on contrary, the reports of microbes’ capability isolated from environmental habitats such as freshwater and wastewater are limited. This research has proved that hydrocarbon degraders are available in the vicinity of the environment and not only limited to contaminated sites. Therefore, further development of the bioremediation technique can facilitate to give an extra dimension to the choices of hydrocarbon degraders’ sources in the efforts to resolve the oil spill contamination.